Арийцы на Ближнем Востоке: конец мифа - Дьяконов, И. M.
Diakonoff, I. M.; Aryans in the Near East: The End of a Myth; engl. Résumé. Besprechungsartikel zu A. Kammenhuber, Die Arier im Vorderen Orient.